"Global warming" versus "climate change": A replication on the association between political self-identification, question wording, and environmental beliefs. (June 2020) - Soutter, Alistair Raymond Bryce; Mõttus, René
Abstract: Climate change is one of the greatest threats to humanity and requires immediate action. Schuldt, Konrath, and Schwarz (2011) suggested that beliefs in environmental phenomena can be influenced by the terminology used to describe it: changing question wording from global warming to climate change resulted in a 6.3 percentage point increase in belief in environmental phenomena. This association was moderated by political self-identification, with Republicans being 16.2 percentage points more likely to believe in climate change than in global warming, with Democrats showing no difference. The potential for connotative meanings to shift over time and the sociopolitical changes since the original study, potential policy and environmental campaign implications, and an expansion of these findings to other countries, motivated an attempt to replicate this important finding. This pre-registered study repeated the original procedures in the United States of America and two other countries (United Kingdom and Australia; total N = 5, 717). Although question wording no longer had a significant effect on beliefs in climate change/global warming, the association of political self-identification with beliefs in environmental phenomena replicated in all three countries, with Conservatives consistently believing less in climate change/global warming than Liberals. The potential impacts of temporal and methodological differences on the discrepancies between this study's and the original's findings are discussed. Highlights: Interaction between question wording and political self-identification did not replicate. Belief in environmental phenomena did not depend on question wording. Political polarisation of belief is evident cross nationally. Conservatives cross-nationally believe less in environmental issues. Belief has increased over time.